Safe Use of Intraspinal Anesthesia in Geriatric Orthopedic Surgery and Its Effect on Coagulation Factors - Jing Xiang; Yi Sun; Jingbo Pi (Journal of Investigative Surgery)
Objective This study aimed to observe the safe use of intraspinal anesthesia in geriatric orthopedic surgery and its effect on coagulation factors.Methods The anesthesia indices, cognitive functions, hemodynamic indicators, along with coagulation function indices were compared. The duration of anesthesia was compared between the two groups. Adverse reactions occurring in the two groups of patients were compared.Results The time to awaken, time to open eyes, time to the verbal statement, the onset of anesthesia, duration of sensory blockade, and duration of motor nerve blockade were shorter while the duration of analgesia was longer in the observation group than in the control group. The observation group’s postoperative Mini-Mental State Examination scores were higher than those of the control group. Heart rate and mean arterial pressure of the patients in the observation group at 10 min after anesthesia and at the end of surgery were lower versus those in the control group. The observation group had lower levels of von Willebrand factor (%) and fibrinogen at 10 min after anesthesia and at the end of surgery than the control group, and lower levels of the thrombin-antithrombin complex at the end of surgery than the control group. The observation group exhibited a lower incidence of adverse reactions in contrast to the control group.Conclusion The application of intraspinal anesthesia in geriatric orthopedic surgery has a significant and remarkable effect, with less impact on patients’ hemodynamics and postoperative cognitive function, and can improve patients’ blood hypercoagulability.